(untitled) (Acta Scientiarum. Animal Sciences, 2026)
A major challenge in soil pollution research is the accumulation of heavy metals from human activities, which threatens environmental integrity and public health. Transport vehicles contribute significantly to metallic particles, such as nickel and cadmium, from the wear and tear of brakes and tires. The study aimed to determine the content of heavy metals in the roadside soils of crowded roads in Mosul city. The study was conducted on 51 roadside soil samples collected from seventeen crowded roads. The samples analyzed by X-ray fluorescence spectrometer. The contamination and level of pollution risk were assessed using the contamination factor, pollution load index, ecological risk, potential risk index, and the degree of contamination. The results of the study revealed that the mean of heavy metals was 2.60, 0.20, 25.87, 36.40, 125.57, 113.05, 8.36, and 5.81 ppm for Pb, Cd, Zn, Cu, Ni, Cr, Co, and As, respectively. The contamination factor values were within no pollution and moderate pollution levels for the majority of elements except Ni, which was within very high pollution levels in some sites, which led to a rise in the degree of contamination. A low risk level was recorded by calculating the potential ecological risk index because the individual ecological risk factor had a low value at all sites. The pollution load index values at all sites were within the pollution level, except for two.